Salivary and plasma cortisol and free testosterone during a winter swimming training season - Rama, L.; Alves, F.; Rosadom F.; Teixeira, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Studies on the impact of training load on endocrine response have led to inconclusive findings. The aim of this study was to measure the response of salivary and plasma cortisol and free testosterone during a swimming winter season, in order to test the sensibility of these markers to training variation, fatigue and adaptation. Methods: 19 well-trained swimmers, 13 men (17,2±1,3 years, 174,9±5,8 height, and 65,8±6,8 mass) and 6 women (15,8±0,8 years, 163,0±9,4 height, 54,6±5,0 mass), were recruited for this study. The training load, volume, intensity and participation in competition events, were monitored during 29 weeks of a winter swimming season. Blood and saliva samples were taken at rest, at the same time of day, before the first afternoon workout of the week (16:00 h), at four testing moments: before the beginning of training season (t1) after the first 7 weeks of incremental training load(t2), after 6 weeks of an intermediate intense training mesocycle (t3) after a major competition (t4). Salivary cortisol and testorone were determined by Elisa and plasma values were determined by Chemiluminescence. At t2, t3 and t4 the swimmers completed a graded swimming protocol (7x200), in order to determine the lactate velocity curve and the associated parameters. In this study we adopted a single group repeated measures design in which athletes served as their own control subjects. All ethical presuppositions that a study of this scope compels have been verified. Results: Training volume was significantly higher at t2 and t4 and intensity increased significantly at t4 (p<0,05). Plasmatic and salivary cortisol showed significant correlation ( r=0,505, to r=0,902; p<0,01) in all testing moments. Male swimmers had higher plasma and salivary cortisol values in harder training phases when compared to t1 (p<0,05). The salivary and free plasmatic testosterone were also significantly correlated ( r=0,703 to 0,747) at the 4 testing moments but showed no variation during the training season. When compared to the beginning of the season, salivary T/C only decreased significantly in t4 (p<0,05), but in the case of plasmatic T/C we found significant lower values in all intermediate moments of the season when compared to the initial one. The results of the graded swimming protocol revealed that the highest maximal and DMax swimming velocity were observed at t3 which coincided with the highest salivary cortisol and lowest T/C values. Conclusion Free Testosterone levels at rest do not seem to be affected by training during the swimming season. High Cortisol levels did not impair the maximal and submaximal performance capacity. The stress induced by hard training phases increased the cortisol values both in plasma and saliva, but a real increased in the magnitude of training load is needed to have a significant impact in salivary cortisol content. In conclusion, salivary cortisol alone, at rest, could be a useful marker of the stress induced by training load.